Cryptic cerebral visual impairment in children. Issue 8 (10th May 2006) - Lowery, R S; Atkinson, D; Lambert, S R
Abstract : Aim: To review the medical records of seven children with a delayed diagnosis of cerebral visual impairment. Methods: The charts of a consecutive series of children examined in a university based ophthalmology clinic with a delayed diagnosis of cerebral visual impairment were reviewed. Their neuroimaging studies were evaluated by a paediatric neuroradiologist. Results: The seven patients ranged in age from 2 years to 10 years at the time of presentation and had acuities ranging from 20/40 to 20/400. Their visual fields ranged from full visual fields to homonymous hemianopias. Neuroimaging findings ranged from subtle occipital lobe abnormalities to obvious cerebral volume loss. Conclusions: Cerebral visual impairment can be cryptic in children with mild visual impairment. Neuroimaging studies and visual field testing can help to differentiate this condition from other causes of visual impairment.